(untitled) (Revista científica Olimpia, 2020)
Breathing is a formidable means of physical and psychic self-regulation that affects emotional states, channels negative emotions and is related to most of the psychic, physical and spiritual vitality. Sports athletes, particularly shorting ones, are demanded a high degree of psychic stability, evidenced by a great capacity of self-control and self-regulation allowing the stable and precise execution of their exercises in training and competitions. For this reason, it is necessary to guide our work through breathing as a means of self-regulation of all these processes towards the search for a moderate stability in their manifestations, helping them to increase their effectiveness in shooting. This work was carried out in the Shooting Range belonging to the EIDE "Pedro Batista" with a sample of 8 Athletes of Shooting Sport Pistol Mode with the objective of optimizing the psychophysiological processes through a breathing system that would act as a method of self-regulation to increasing the effectiveness and performance of the athletes of Shooting Sports. It was verified that the system of breathing exercises contributed to the optimization of the psychophysiological processes in the athletes of Shooting Sport Pistol Mode and it was determined that with the application of the exercise system the performance was raised to 35%, from an 8th place reached in the previous competition they improved to a 5th National place.